Prevalence and Associated Factors of Diabetes Mellitus in Puerto Rican Adults: Behavioral Risk Factor Surveillance System, 1999 - Pérez-Cardona, Cynthia; Pérez-Perdomo, Rosa (Puerto Rico Health Sciences Journal, 2013)
See manuscript